Current issues in allogeneic islet transplantation. Issue 5 (October 2017) - Chang, Charles A.; Lawrence, Michael C.; Naziruddin, Bashoo
Abstract : Purpose of review: Transplantation of allogenic pancreatic islets is a minimally invasive treatment option to control severe hypoglycemia and dependence on exogenous insulin among type 1 diabetes (T1D) patients. This overview summarizes the current issues and progress in islet transplantation outcomes and research. Recent findings: Several clinical trials from North America and other countries have documented the safety and efficacy of clinical islet transplantation for T1D patients with impaired hypoglycemia awareness. A recently completed phase 3 clinical trial allows centres in the United States to apply for a Food and Drug Administration Biologics License for the procedure. Introduction of anti-inflammatory drugs along with T-cell depleting induction therapy has significantly improved long-term function of transplanted islets. Research into islet biomarkers, immunosuppression, extrahepatic transplant sites and potential alternative beta cell sources is driving further progress. Summary: Allogeneic islet transplantation has vastly improved over the past two decades. Success in restoration of glycemic control and hypoglycemic awareness after islet transplantation has been further highlighted by clinical trials. However, lack of effective strategies to maintain long-term islet function and insufficient sources of donor tissue still impose limitations to the widespread use of islet transplantation. In the United States, wide adoption of this technology still awaits regulatory approval and, importantly, a financial mechanism to support the use of this technology.